2011
DOI: 10.5194/acp-11-2569-2011
|View full text |Cite
|
Sign up to set email alerts
|

Transport analysis of ozone enhancement in Southern Ontario during BAQS-Met

Abstract: Abstract. Twice-daily ozonesondes were launched from Harrow, in southwestern Ontario, Canada, during the BAQSMet (Border Air Quality and Meteorology Study) field campaign in June and July of 2007. A co-located radar windprofiler measured tropopause height continuously. These data, in combination with continuous surface ozone measurements and geo-statistical interpolation of satellite ozone observations, present a consistent picture and indicate that a number of significant ozone enhancements in the troposphere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…These results emphasize the importance of photochemistry within the lower troposphere during spring and summer. The relative contribution of stratospheric ozone to the tropospheric ozone budget is a controversial issue and has been debated for many years (e.g., Kim and Lee, 2010;He et al, 2011). Our analysis shows that both stratospheric downward transport and photochemical production within the troposphere influence the distribution of tropospheric ozone over Beijing.…”
Section: The Seasonality Of Tropospheric Ozonementioning
confidence: 85%
“…These results emphasize the importance of photochemistry within the lower troposphere during spring and summer. The relative contribution of stratospheric ozone to the tropospheric ozone budget is a controversial issue and has been debated for many years (e.g., Kim and Lee, 2010;He et al, 2011). Our analysis shows that both stratospheric downward transport and photochemical production within the troposphere influence the distribution of tropospheric ozone over Beijing.…”
Section: The Seasonality Of Tropospheric Ozonementioning
confidence: 85%
“…Initial North American domain simulated surface O 3 was biased +15 ppb compared to observations. Vertical O 3 profiles at Harrow (He et al, 2011) showed that the model bias was even greater in the upper troposphere. Makar et al (2010a) used ozonesonde data to evaluate the model's prediction of the O 3 vertical column, noting that middle tropospheric concentrations had large positive biases.…”
Section: Evaluating the Model Capability To Simulate O 3 Particle Fmentioning
confidence: 99%
“…Vertical information was obtained at Harrow using ozonesondes released every 12 h (He et al, 2011), and via a wind profiler near Harrow (Hocking, 1997). Vertical information at Ridgetown was obtained via tethersonde profiling of O 3 and meteorology on select days, a scanning LIDAR ) and a MAX-DOAS system (Halla et al, 2011) for NO 2 and Aerosol Optical Depth (AOD).…”
Section: Fixed Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the simulations were driven by the NCEP FNL data. This model has been extensively validated (Stohl et al, 1998;Cristofanelli et al, 2003) and widely used in studies of the influence of various meteorological processes on pollution transport (Cooper et al, 2004(Cooper et al, , 2005(Cooper et al, , 2006Hocking et al, 2007;Ding et al, 2009;Barret et al, 2011;He et al, 2011;Chen et al, 2012). In running FLEXPART, a large number of particles are released from defined locations (latitude, longitude, and altitude) at a time.…”
Section: The Flexpart Trajectory Modelmentioning
confidence: 99%